Analyzing MT Arman 11 Case: Dispute Settlement in Seizure of Ship's Action under International Law - Gunawan, Yordan; Fathi, Muhammad; Ghiffara, Mustafad (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
On October 7, 2023, the Indonesian Coast Guard's recent seizure of the Iranian-flagged MT Arman 114 vessel has highlighted the legal complexities involved in enforcing maritime security in the Exclusive Economic Zone (EEZ). This article examined the United Nations Convention on the Law of the Sea (UNCLOS) 1982 as the main legal framework regulating such occurrences. Flag state sovereignty typically regulates vessels, but UNCLOS 1982 grants coastal states such as Indonesia the authority to deal with infringements occurring within their Exclusive Economic Zones (EEZs), such as illicit oil transfers and actions that pose a threat to national security. The article explored Part XV of UNCLOS 1982, which elucidated the many systems for resolving disputes, ranging from voluntary ways to obligatory procedures, including esteemed organizations such as the International Tribunal for the Law of the Sea (ITLOS) and the International Court of Justice (ICJ). The author therefore uses normative legal research methods to highlight the importance of strong legal structures such as UNCLOS 1982 in facing impending maritime security difficulties in the Exclusive Economic Zone (EEZ), encouraging collaboration and non-violent resolution of complex issues such as ship seizures. The results show that, in the situation of the seizure of MT Arman 114, depending on the alleged violations and the outcome of negotiations between Indonesia and Iran, it may be appropriate to use UNCLOS 1982 dispute resolution procedures, such as ITLOS or ICJ, to achieve justice. and valid international decisions.